PENERAPAN ALGORITMA KNUTH-MORRIS-PRATT DALAM PENDATAAN JEMAAT GEREJA METHODIST INDONESIA (GMI) ELSHADAI PEKANBARU - Renta Wasni Putri; Alyauma Hajjah (STMIK KAPUTAMA, 2022)
Providing stewardship for people who come to the church, the Indonesian Methodist Church (GMI) Elshadai Pekanbaru which is located on Jl.Abdul Malik Gg Matador Pekanbaru Kulim, this church is a place of worship for Wesley Christians. Where this church is in the organization data structuring procedure that is running in the church is still manual in data collection of its congregation. With the growing need for information accompanied by technological advances in producing good information, the church also needs an information system that can support and assist in church development. This study aims to be able to design a php computerized information system with the waterfall or SDLC method that can support and provide informationabout the church's daily news, as well as the application of the knuth-morris-pratt algorithm tosearch for information on church members or church members. So that the results to beobtained can show that using the knuth-morris-prat algorithm method can work very well insearching a string.